Learning Management Of Islamic Teachers In Millenial Era - Sri Nurabdiah Pratiwi; Inom Nasution (Proceeding International Seminar of Islamic Studies, 2019)
Millnieal era is closely related to technology which cause changing in thought, behaviour and social life of human being. This is happened to almost all of human life, and no nation can avoid it. There are many negative things appear if this technology is not well managed, mainly in the learning process which is tightly connected to manner and moral. One of many ways to anticipate the negative impact of millenial era is through the role of the Islamic teachers. Since it has been said in Quran, we have to be ready to face the technology advances. To make Islam as part of students daily life, it needs a management system that can answer the social problems in technology through the learning process. Therefore, the application of technology in learning management is expected to be able to give a suitable learning patterns; put forwards the technology, yet not leaving the moral, ethic and culture of politeness of Indonesian, which, as the result, is in harmony with the National Educations goal.